PRINSIP ANDRAGOGI DALAM PELATIHAN MENTOR PEMAGANGAN GUNA MENGHASILKAN REKOMENDASI KOMPETEN - Yustina Erti Pravitasmara Dewi; Titi Agustina (Universitas Sanata Dharma, 2021)
The training for workplace trainers in apprenticeship is at the heart of our aim of the community service. Training activities were carried out in Semarang and Solo in 2020. The training utilized the principle of andragogy and gaining success with 50 certified workplace trainers. The primary challenging part in conducted training for workplace trainers was about the degree of quantity and quality of the portfolio as competencies evidence. Applying the andragogy principle in this training with ice-breaking games, controlling participants' progress portfolio are among the success factors. The key performance indicator for successful training is based on the results of an assessment competency that provides competent recommendations for all training participants. This article also reveals the use of a model that applies creative andragogy to competency-based training that emphasizes the individual's ability to absorb learning.